1991
DOI: 10.12693/aphyspola.80.571
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorotational Averaging of EPR Spectrum of Cu(II)O5Complex in YBa2Cu3O7-δin Low Temperatures

Abstract: In low temperatures the condensation of oxygen was found to occur at 05 site in an elementary cell of YBa2Cu3O7-δ being the fifth ligand forming the CuO5 complex around Cul copper in chain. This change of coordinantion from CuO4 to CuO5 is the origin of a pseudorotation related to a strong vibronic coupling of two distorted configurations: a tetragonal pyramid C4v and a trigonal bipyramid D3h, which yields a pseudocubic EPR spectrum in low temperatures. The averaged spectroscopic splitting coefficient is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For Φw = 0.2, the measured g-factor equal to g 2.13 is the average of g11 and g1. In this case the co-ordination is the superposition of the two orbital s t at es │x2 -y2) and 13z2 -r 2 > a s d i s c u s s e d i n [ 8 ] . The changes in the g-factor and the increase in the EPR line width and intensity are caused by the progress of the reaction between YBCO and PST when Φw < 0.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Φw = 0.2, the measured g-factor equal to g 2.13 is the average of g11 and g1. In this case the co-ordination is the superposition of the two orbital s t at es │x2 -y2) and 13z2 -r 2 > a s d i s c u s s e d i n [ 8 ] . The changes in the g-factor and the increase in the EPR line width and intensity are caused by the progress of the reaction between YBCO and PST when Φw < 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…For Φw = 0.2, the measured g-factor equal to g 2.13 is the average of g ││ and 91. In this case the co-ordination is the superposition of the two orbital states │ x 2 -y 2 ) a n d 1 3 z 2 -r 2 ) a s d i s c u s s e d i n [ 8 ] . The decay of the superconductivity is apparent from the measurements of the superconducting volume ratio Φv.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is applicable only to the "high-temperature" range (T > 60 K), whereas the origin of the "low-temperature" EPR line (T < 40 K) [3,5] can be quite different. To solve this problem an additional investigation is needed.…”
Section: Eleetron Spin-lattiee Relaxationmentioning
confidence: 94%
“…The EPR spectrum in these substances is well known (see for example [3][4][5]) but there is no commonly accepted viewpoint conceming its nature. Some authors [4,5] ascribe the observed asymmetric line to various structural defects including oxygen vacancies; others [3] consider this EPR spectrum as originated from impurity phases, primarily from the so-called "green phase" Y2BaCuOs.…”
Section: Eleetron Spin-lattiee Relaxationmentioning
confidence: 99%